Effect of Moringa oleifera leaf polysaccharide on the composition of intestinal microbiota in mice with dextran sulfate sodium-induced ulcerative colitis - Husien, Hosameldeen Mohamed; Rehman, Shahab Ur; Duan, Zhenyu; Wang, Mengzhi (Frontiers in Nutrition, 2024)
Moringa oleifera (M. oleifera) is a natural plant that has excellent nutritional and medicinal potential. M. oleifera leaves (MOL) contain several bioactive compounds.The aim of this study was to evaluate the potential effect of MOL polysaccharide (MOLP) on intestinal flora in dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) mice. DSS-induced colitis was deemed to be a well-characterized experimental colitis model for investigating the protective effect of drugs on UC. In this study, we stimulated the experimental mice with DSS 4% for 7 days and prepared the high dose of MOLP (MOLP-H) in order to evaluate its effect on intestinal flora in DSS-induced UC mice, comparing three experimental groups, including the control, DSS model, and DSS+MOLP-H (100 mg/kg/day). At the end of the experiment, feces were collected, and the changes in intestinal flora in DSS-induced mice were analyzed based on 16S rDNA high throughput sequencing technology. The results showed that the Shannon, Simpson, and observed species indices of abundance decreased in the DSS group compared with the control group. However, the indices mentioned above were increased in the MOLP-H group. According to beta diversity analysis, the DSS group showed low bacterial diversity and the distance between the control and MOLP-H groups, respectively. In addition, compared with the control group, the relative abundance of Firmicutes in the DSS group decreased and the abundance of Helicobacter increased, while MOLP-H treatment improves intestinal health by enhancing the number of beneficial organisms, including Firmicutes, while reducing the number of pathogenic organisms, such as Helicobacter. In conclusion, these findings suggest that MOLP-H may be a viable prebiotic with health-promoting properties.